2014
DOI: 10.1111/febs.12871
|View full text |Cite
|
Sign up to set email alerts
|

The Kv1.3 potassium channel is localized to the cis‐Golgi and Kv1.6 is localized to the endoplasmic reticulum in rat astrocytes

Abstract: The functions of voltage‐gated potassium (Kv) channels in neurons have been well defined, whereas their roles in glial cells are not fully understood. Kv1.1, Kv1.3 and Kv1.6 are endogenously expressed in C6 astrocytoma cells, but their trafficking and subcellular localization have not been well studied. In C6 cells, Kv1.1 was localized to the cell surface, Kv1.3 was predominantly localized in the cis‐Golgi, and Kv1.6 was enriched in the endoplasmic reticulum. Disruption of the Golgi stacks with brefeldin A tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…This intracellular shift is consistent with the reported movement of Kv1.3 protein within CNS microglia exposed to direct current stimulation during proliferation in vitro (Kotecha and Schlichter, 1999). As predicted from the literature (Zhu et al, 2014), we also found that callosal astrocytes express Kv1.3, albeit at a lower level than microglia (Fig. 10B).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This intracellular shift is consistent with the reported movement of Kv1.3 protein within CNS microglia exposed to direct current stimulation during proliferation in vitro (Kotecha and Schlichter, 1999). As predicted from the literature (Zhu et al, 2014), we also found that callosal astrocytes express Kv1.3, albeit at a lower level than microglia (Fig. 10B).…”
Section: Resultssupporting
confidence: 90%
“…Kv1.3 protein mobilization during microglial activation not only demonstrates the functional relevance of Kv1.3 channels, but also suggests that their susceptibility to selective channel blockers could alter microglial reactivity after white matter injury. In this context, we also probed for Kv1.3 by WB in callosal mixed glial cultures ( data not shown ), where we observed a single 55kD Kv1.3 species, smaller than the predicted 68-70 kD monomer or the 160 kD dimerized channel protein (Kotecha 1999; Fadool 1997; Zhu, 2014). Since higher kD tyrosine phosphorylated forms of the channel show functional suppression (Colley and Fadool, 2004), we speculate that the 55kD in callosal glial cultures may represent an active, less phosphorylated Kv1.3 form.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…expression of Kv1.3 in mitochondrial and plasma membranes, had already been found in breast cancer MCF-7, prostate cancer PC3, osteosarcoma SAOS-2, melanoma B16F10, Jurkat T cell lymphoma [22,26,27] and pancreas carcinoma [28]. In addition, recent data indicate the presence of Kv1.3 also in cis-Golgi [29] and in the nuclear membrane [30], which is also consistent with the present studies. The function of the cis-Golgi-located channels is unknown, while nuclear Kv1.3 has been suggested to impact on transcription factor activation via regulation of the nuclear membrane potential.…”
Section: Discussionsupporting
confidence: 93%
“…Kv1.3 was located to the cis-Golgi membranes as well [29] and, recently, to the nuclear membrane [30] where it seems to be involved in regulation of transcription. Expression of the channel in the IMM seems to correlate with that in the PM (e.g.…”
Section: Introductionmentioning
confidence: 99%